Synthesis and thermal conductivities of ZnIn 2Te 4 and CdIn 2Te 4 with defect-chalcopyrite structure - Suriwong T. (2014)
ZnIn 2Te 4 and CdIn 2Te 4 have a defect-chalcopyrite tetragonal crystal structure with structural vacancies. In order to investigate the effects of vacancies on the lattice thermal conductivity (κ lat), single phase samples of ZnIn 2Te 4 and CdIn 2Te 4 were synthesized and their κ lat values were examined in the temperature range from room temperature to 850 K. The κ lat data for ZnIn 2Te 4 and CdIn 2Te 4 were compared with those of Zn- and Cd-series chalcopyrite compounds with no vacancies. The results revealed that the presence of vacancies alone in the defect-chalcopyrite structure does not result in effective phonon scattering. © 2011 Elsevier B.V. All rights reserved.